A Culturally Adaptive Model of Rehabilitative Justice across Secular and Islamic Approach - Purnama Sari, Imma; Haiti, Diana; Nurunnisa (DIKTUM: Jurnal Syariah dan Hukum, 2025)
Background: Contemporary criminal justice systems are increasingly challenged to balance punitive measures with rehabilitative goals, particularly in culturally diverse and legally pluralistic societies. While secular models, such as those found in Norway, emphasize rights-based rehabilitation, Islamic-majority countries like Malaysia and Indonesia navigate complex intersections between religious ethics and secular legal frameworks. Purpose: This study aims to investigate how secular and Islamic approaches to rehabilitative justice are operationalized across three jurisdictions—Norway, Malaysia, and Indonesia—and to identify pathways for integrating ethical, institutional, and empirical insights into a cohesive, context-sensitive reform model Methods: Employing a qualitative-comparative design, the research combines normative legal analysis, socio-legal investigation, and thematic content analysis. Primary sources include national legal documents, prison policies, international reports, and expert interviews Results: Findings reveal that Norway’s secular rehabilitative system achieves strong empirical outcomes through individualized, rights-based practices; Malaysia partially integrates Islamic ethical principles into correctional programs with measurable, though uneven, success; while Indonesia’s fragmented legal system relies largely on grassroots religious initiatives without formal institutional integration, resulting in persistently high recidivism Implication: The study contributes both theoretically and practically by demonstrating that ethical pluralism—rather than creating fragmentation—can enrich rehabilitative justice if systematically integrated. For policymakers, the findings suggest the need to embed both secular human rights and religious ethical commitments into penal reform strategies, particularly in Muslim-majority and legally hybrid societies. Originality: This article advances the literature by offering one of the few cross-jurisdictional, empirically grounded comparative studies that bridge secular and Islamic rehabilitative frameworks, challenging binary understandings and proposing an integrative, ethically robust model for justice reform